Equilibrium bay shape approach for analysis of shoreline in Myanmar - Khin Nathar Aung Myint Htay; Sutat Weesakul; Babel, Mukand Singh; Sarawut Ninsawat; Somchai Chonwattana; DAAD (Pathum Thani, Thailand : Asian Institute of Technology, 2019)
Total of 106 bays along the coastline of Myanmar are analyzed using equilibrium bay shape equation in this study and are classified into three groups: static equilibrium (SEB), dynamic equilibrium (DEB) and unstable. Only the geometrical planform which can be obtained from satellite images is used for the analysis of this study. Littoral cells along the coastline of Myanmar are identified based on the geographical planform only. Analysis of equilibrium bays in the littoral cells is conducted in order to identify the areas where erosion or accretion can occur as well as long term equilibrium can exist. Areas where changes in the sediment supply can affect the stability of the shoreline planform are also determined. Some characteristics of the bays are compared and contrast to those of bays in neighbouring countries (Thailand and Vietnam) using the results of previous studies in order to indicate the overall shoreline changes along the continuous shoreline. For the stabilization of the unstable bays, two methods are proposed: headland control method and sediment control method. Headland control method is to adjust the upcoast control point and it can be used for both static and dynamic condition. Both methods are used for the stabilization of dynamic unstable bays and the efficiency index (El) of using each method is compared.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Water Engineering and Management
Thesis (M.Eng.) - Asian Institute of Technology, 2019
Keywords: Equilibrium (Physiology) -- Analysis; Equilibrium -- Myanmar; Shorelines -- Myanmar